Способ получения 2,4,6,8-тетраазабицикло [3.3.0] октан-3,7-диона - Шелудяков О. А.; Яговкин А. Ю.; Бакибаев А. А. Абдигали Абдиманапович; Филимонов В. Д. Виктор Дмитриевич; Сологуб А. П.; Бычков И. А.; Новожеева Т. П.
опубл. 20.07.96, Бюл. № 20